The Efficacy of Schwann-Like Differentiated Muscle-Derived Stem Cells in Treating Rodent Upper Extremity Peripheral Nerve Injury. Issue 4 (11th August 2021) - Xun, Helen; Yesantharao, Pooja; Musavi, Leila; Quan, Amy; Xiang, Sinan; Alonso-Escalante, Jose C.; Wang, Howard; Tammia, Markus; Cetinkaya-Fisgin, Aysel; Lee, W. P. Andrew; Brandacher, Gerald; Kumar, Anand; et al.
Abstract : Background: There is a pressing need to identify alternative mesenchymal stem cell sources for Schwann cell cellular replacement therapy, to improve peripheral nerve regeneration. This study assessed the efficacy of Schwann cell–like cells (induced muscle-derived stem cells) differentiated from muscle-derived stem cells (MDSCs) in augmenting nerve regeneration and improving muscle function after nerve trauma. Methods: The Schwann cell–like nature of induced MDSCs was characterized in vitro using immunofluorescence, flow cytometry, microarray, and reverse-transcription polymerase chain reaction. In vivo, four groups ( n = 5 per group) of rats with median nerve injuries were examined: group 1 animals were treated with intraneural phosphate-buffered saline after cold and crush axonotmesis (negative control); group 2 animals were no-injury controls; group 3 animals were treated with intraneural green fluorescent protein–positive MDSCs; and group 4 animals were treated with green fluorescent protein–positive induced MDSCs. All animals underwent weekly upper extremity functional testing. Rats were euthanized 5 weeks after treatment. The median nerve and extrinsic finger flexors were harvested for nerve histomorphometry, myelination, muscle weight, and atrophy analyses. Results: In vitro, induced MDSCs recapitulated native Schwann cell gene expression patterns and up-regulated pathways involved in neuronal growth/signaling. In vivo, green fluorescent protein–positive induced MDSCs remained stably transformed 5 weeks after injection. Induced MDSC therapy decreased muscle atrophy after median nerve injury ( p = 0.0143). Induced MDSC- and MDSC-treated animals demonstrated greater functional muscle recovery when compared to untreated controls (hand grip after induced MDSC treatment: group 1, 0.91 N; group 4, 3.38 N); p < 0.0001) at 5 weeks after treatment. This may demonstrate the potential beneficial effects of MDSC therapy, regardless of differentiation stage. Conclusion: Both MDSCs and induced MDSCs decrease denervation muscle atrophy and improve subsequent functional outcomes after upper extremity nerve trauma in rodents.